Control of Water Inrush from Longwall Floor Aquifers Using a Division Paste Backfilling Method. (25th November 2021) - Chang, Qingliang; Yao, Xingjie; Ge, Shiguo; Xu, Ying; Sun, Yuantian
Abstract : Aiming at the problem of the safety mining problems of longwall paste filling working face under buildings on high confined water in the Daizhuang Coal Mine, the paste filling mining method was used. A series of theoretical analyses, numerical simulations, and field measurements were applied. The results showed that when the filling interval of the working face increases from 1.2 m to 3.6 m, no significant change is found in the depth of the perforated plastic zone of the floor strata. According to the types of water-conducting cracks in the floor strata of the working face 11607, the floor strata are divided into the floor intact area, the structure developed area, and the floor weak area. Based on that, the measures for preventing and controlling the floor failure in the paste filling working face are proposed. Furthermore, the failure depth of the floor of the test working face was detected by the on-site water injection method, and the results showed that the maximum failure depth of the floor of the test working face was about 3 m.